Universities and Public Libraries Supporting Student Success: An Exploratory Study. Issue 2 (3rd April 2017) - Howlett, Alisa; Partridge, Helen; Belov, Rebecca
Abstract: As universities seek new ways to engage and support students in their learning, in Australia, students from regional and remote areas pose a challenge for universities given their geographical, social and technological isolation compared with their metropolitan counterparts. Much of the literature that address challenges associated with distance learning focus on teaching, course design and ways of accessing learning materials. Little is known about the provision of learning support services. Public libraries are well placed within their communities to assist university students with their learning needs. The aim of this research was to explore the idea of universities and public library services working together to support regional student success. The University of Southern Queensland provided the context for this study. Semi-structured interviews with representatives from public library services in regional areas of Queensland were conducted to find out what service is currently being provided to students; challenges, opportunities and related issues. Thematic analysis was used to identify themes that told the 'story' within the data. Findings suggest there is an opportunity for universities and public libraries to work together to support regional student success, and that this opportunity is worthy of further discussion and exploration.